2018
DOI: 10.1371/journal.pone.0200433
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz type protease inhibitor EgKI-1 from the canine tapeworm Echinococcus granulosus as a promising therapeutic against breast cancer

Abstract: EgKI-1, a member of the Kunitz type protease inhibitor family, is highly expressed by the oncosphere of the canine tapeworm Echinococcus granulosus, the stage that is infectious to humans and ungulates, giving rise to a hydatid cyst localized to the liver and other organs. Larval protoscoleces, which develop within the hydatid cyst, have been shown to possess anti-cancer properties, although the precise molecules involved have not been identified. We show that recombinant EgKI-1 inhibits the growth and migrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…In vitro scratch wound assays were carried out to determine the effect of SEA extracted from control and CRISPR/Cas9 mutated eggs [80,81]. HSC cells (LX-2) were cultured in completed medium containing high glucose EMDM (Invitrogen), 2% fetal bovine serum (FBS), 1% glutamax and 1% Pen/strep.…”
Section: In Vitro Scratch Wound Assaysmentioning
confidence: 99%
“…In vitro scratch wound assays were carried out to determine the effect of SEA extracted from control and CRISPR/Cas9 mutated eggs [80,81]. HSC cells (LX-2) were cultured in completed medium containing high glucose EMDM (Invitrogen), 2% fetal bovine serum (FBS), 1% glutamax and 1% Pen/strep.…”
Section: In Vitro Scratch Wound Assaysmentioning
confidence: 99%
“…However, the alum-based adjuvant employed in the latter study is potentially confounding (Ranasinghe and McManus, 2018), since alum may induce anticancer effect through selectively stimulation of Th2 immune response (Didierlaurent et al, 2009). Recently, a research group found that the Kunitz-type protease inhibitor EgKI-1, a potent chymotrypsin and neutrophil elastase inhibitor highly expressed by oncosphere of E. granulosus (Ranasinghe et al, 2015), could inhibit several human cancers from growth and migration, probably through disrupting cell cycle and inducing apoptosis of cancer cells, without affecting normal cell growth in vitro (Ranasinghe et al, 2018). Meanwhile, EgKI-1 treatment could restrict experimental triple negative breast cancer growth in a BABL/c mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Available evidences have led to a hypothesis that E. granulosus may induce anticancer effect through hydatid molecules, especially the protoscolex ES molecules. Although the specific molecules and the underlying mechanisms remain largely unknown, EgKI-1, a potent chymotrypsin and neutrophil elastase inhibitor highly expressed by E. granulosus (Ranasinghe et al, 2015), was able to induce anticancer effect both in vitro and in animal models (Ranasinghe et al, 2018). In addition to the potent inhibitory effect on neutrophil elastase, which plays a crucial role in cancer metastasis, EgKI-1 can also induce anticancer effect by directly inhibiting tumor growth, probably through disrupting cell cycle progression, thus increasing cancer cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant EgKI-1 has been produced and its activity was tested against a range of human cancer cell lines, including breast adenocarcinoma, pharynx adenocarcinoma, cervical epithelial adenocarcinoma, and melanoma [11,38,40]. It was shown that EgKI-1 induced apoptosis in breast cancer cells after 24 h in a dose-dependent manner [39].…”
Section: Autophagymentioning
confidence: 99%
“…Based on that assumption, one could speculate that anti-cancer therapeutic approaches, including radiotherapy, should be tested to induce regulated cell death (RCD) of the parasite [25]. The second option is to address the issue of pro-apoptotic effects of HCF produced during infection of the intermediate host, and to test the hypothesis of potential value of certain specific compounds of this fluid as therapeutic agents for human cancers, including melanoma and breast cancer [11,14,16,39,51]. These two approaches may open an extensive research area, provided preliminary results obtained to date are consolidated and confirmed in large controlled studies.…”
Section: Introductionmentioning
confidence: 99%